Financial abuse and intimate partner violence in the Puerto Rican context - Silva-Martínez, Elithet; Vázquez-Pagán, Jenice M. (Prospectiva. Revista de Trabajo Social e Intervención Social, 2019)
Research on intimate partner violence has focused on the dimensions of physical, emotional, and sexual abuse.  This article proposes to state financial abuse as an additional dimension.  Financial abuse presents some specific characteristics that significantly affect the lives of survivors and their children.  It is important to define these and propose ways to take action through social work practice and social policies.  To fulfill this objective, it is necessary to develop a research agenda that contributes to the development of knowledge in this area.  In the same way, it is necessary that states develop and implement, in an effective manner, social policies that address financial abuse as a different dimension of intimate partner violence and upon recognizing it, achieve the financial empowerment of women survivors of gender-based violence and their children.  In this work, we will present Puerto Rico’s experience and offer some recommendations on this particular matter.